Consideration For Transference in The Context of Trilingualism (Texas Journal of Philology, Culture and History, 2021)
Today, learning languages are becoming common all over the world. It is worth Studying not only one foreign language, but also 3 and more languages in order to be successful person in every career/field. For this reason, this article is devoted to consideration for transference in the context of trilingualism.